A novel FTY720 analogue targets SET-PP2A interaction and inhibits growth of acute myeloid leukemia cells without inducing cardiac toxicity. (1st January 2020) - Vicente, Carmen; Arriazu, Elena; Martínez-Balsalobre, Elena; Peris, Irene; Marcotegui, Nerea; García-Ramírez, Patricia; Pippa, Raffaella; Rabal, Obdulia; Oyarzábal, Julen; Guruceaga, Elizabeth; Prósper, Felipe; Mateos, María C.; et al.
Abstract: Acute myeloid leukemia (AML) is an aggressive disease associated with very poor prognosis. Most patients are older than 60 years, and in this group only 5–15% of cases survive over 5 years. Therefore, it is urgent to develop more effective targeted therapies. Inactivation of protein phosphatase 2 A (PP2A) is a recurrent event in AML, and overexpression of its endogenous inhibitor SET is detected in ~30% of patients. The PP2A activating drug FTY720 has potent anti-leukemic effects; nevertheless, FTY720 induces cardiotoxicity at the anti-neoplastic dose. Here, we have developed a series of non-phosphorylable FTY720 analogues as a new therapeutic strategy for AML. Our results show that the lead compound CM-1231 re-activates PP2A by targeting SET-PP2A interaction, inhibiting cell proliferation and promoting apoptosis in AML cell lines and primary patient samples. Notably, CM-1231 did not induce cardiac toxicity, unlike FTY720, in zebrafish models, and reduced the invasion and aggressiveness of AML cells more than FTY720 in zebrafish xenograft models. In conclusion, CM-1231 is safer and more effective than FTY720; therefore, this compound could represent a novel and promising approach for treating AML patients with SET overexpression. Highlights: CM-1231 reactivates PP2A and shows potent anti-leukemic activity in AML cell lines. CM-1231 restores PP2A activity by disrupting the binding between SET and PP2A. CM-1231 did not induce cardiac toxicity, unlike FTY720, in zebrafish embryo models. CM-1231 reduces invasion of AML cells more than FTY720 in zebrafish xenograft models. CM-1231 inhibits the growth of patient derived AML cells more efficiently than FTY720.